Is it Beneficial to be Included in a Sustainability Stock Index? A Panel Data Study for European Firms - Andreas Ziegler (ETH Zurich, CER-ETH - Center of Economic Research, 2009)
This paper empirically examines the effect of the inclusion in one of the most prominent sustainability stock indexes, namely the Dow Jones Sustainability World Index (DJSI World), on corporate financial performance. On the basis of panel data for European firms that were included in the Dow Jones Stoxx 600 Index over time, our micro-econometric analysis confirms the relevance of unobserved firm heterogeneity since the validity of restricted pooled regression models is statistically rejected in favor of random or fixed effects models. As a consequence, the strong positive impacts of the inclusion in the DJSI World on return on assets and Tobin's Q in pooled regression models become weaker and less robust in the case of return on assets and even insignificant for Tobin's Q in the flexible panel data models that include unobserved firm heterogeneity. Therefore, we conclude that the application of misspecified panel data approaches, similar to cross-sectional models, can lead to biased parameter estimates and thus to premature conclusions with respect to the impact of corporate sustainability performance on financial performance. Our estimation results can be explained by the high number of confounding financial effects of corporate environmental or social activities. Another explanation for the predominant weak or neutral impacts of the inclusion in the DJSI World could be the composition of this stock index, which is influenced by factors that need not necessarily be directly connected to corporate environmental or social activities.
Keywords: M14; Q01; Q56; C23; 330; Sustainability stock index; Corporate environmental and social activities; Corporate financial performance; Panel data models; Aktienindex; Corporate Social Responsibility; Unternehmensfinanzierung; Börsenkurs; Kapitaleinkommen; Tobins Q; Panel; Schätzung; Europa